2019
DOI: 10.3390/su11154153
|View full text |Cite
|
Sign up to set email alerts
|

Financial Constraints and R&D Investment: The Moderating Role of CEO Characteristics

Abstract: How CEOs with different characteristics act differently on R&D investment under the condition of financial constraints is an important but understudied question towards firms’ sustainable innovation. Employing the dataset from China-Enterprise Survey 2012 of the World Bank, this study tests the impact of financial constraints on firms’ R&D investment and the moderating role of CEO characteristics. Empirical results show that: (1) firm’s financial constraints have a significant restricting effect on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 59 publications
(142 reference statements)
2
21
0
Order By: Relevance
“…Each CEO has a unique motivational orientation that can be better understood through regulatory focus theory. This insight, combined with the findings of previous studies that have considered the influence of other individual characteristics on R&D spending (i.e., Barker & Mueller, 2002; Cheng, 2004; Serfling, 2014; Yin et al, 2019; Yunlu & Murphy, 2012), suggests the importance of boards recognizing individual differences in CEOs when setting executive compensation packages. In part, applying the same compensation practices for two people with different regulatory foci may have unique and potentially unintended consequences.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Each CEO has a unique motivational orientation that can be better understood through regulatory focus theory. This insight, combined with the findings of previous studies that have considered the influence of other individual characteristics on R&D spending (i.e., Barker & Mueller, 2002; Cheng, 2004; Serfling, 2014; Yin et al, 2019; Yunlu & Murphy, 2012), suggests the importance of boards recognizing individual differences in CEOs when setting executive compensation packages. In part, applying the same compensation practices for two people with different regulatory foci may have unique and potentially unintended consequences.…”
Section: Discussionmentioning
confidence: 56%
“…CEO characteristics, in particular, have been a focal consideration when examining R&D spending (Barker & Mueller, 2002) because of CEOs’ prominent influence on strategy (Finkelstein et al, 2009). In turn, prior research has examined several surface‐level CEO characteristics—including age, gender, educational background, and tenure—to predict R&D spending (Barker & Mueller, 2002; Cheng, 2004; Serfling, 2014; Yin et al, 2019; Yunlu & Murphy, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the following studies identified that directors' gender affected the firm's R&D investment. Despite the common sense that women tend to be risk-averted, researchers have found that female directors in the boardroom actually invest more in R&D activities compared with their male counterparts [25][26][27]. Age is another determinant.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…The analysis conducted by Cheung et al on SMEs demonstrated that R&D collaboration has a positive effect on technical performance, emphasizing the importance of industry-academic collaboration for SMEs [18]. As such, R&D collaboration is recognized as a key strategy for acquiring important external knowledge (technology) [19].…”
Section: Introductionmentioning
confidence: 99%